Strategia produktu na rynku Unii Europejskiej na przykładzie przedsiębiorstw przetwórstwa mięsnego z województwa lubuskiego - Barska, Anetta (The Product Strategy on the European Union Market on Meat Processing Enterprises Example from Lubuskie Voivodship, 2005)
The author's reflection purpose is an appointment of product strategies possibilities to apply by meat processing enterprises on the market of the European Union. In the study, three possible approaches are pointed: standardization of the product, partial diversity and total differential. Their faults and advantages are discussed, also factors determining their application are analysed. Because of the limited framing of the study, the author presents only some elements of the product strategy - the package and the trade mark. The results from marketing examinations realized among 49 meat processing companies from areas of the Lubuskie voivodship are utilized in the study.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 30-37